An investigation of molecular dynamics for simple liquids - Utterson, JNFW (2023)
This thesis contains work expanding the theoretical understanding of molecular dynamics used to aid the study of simple liquids. It does so by focusing on investigating forces, which govern the dynamics of manybody systems. We loosely address three questions: How can we categorise force distributions? What can we gauge from force data? When do forces obey Newton’s third law?